Análisis del discurso periodístico - Fonte Zarabozo, Irene (Enunciación, 2006)
In this article i present a method of analysis of journalistic discourse based on historical researh about Cuban newspapers of the beging of the 20th century. Such research was aimed originally at examining the discursive and ideological processes surrouding the difficult formation of the Cuban Republic. The methodology that i present here is based on the political actors in certain situations. I also analize instances of linguistics phenomena that prove to be relevant for the creation of lines of meaning throughout the examined corpus.